Development of Accelerated Test Method to Evaluate the Long-Term Thermal Performance of Fumed-Silica Vacuum Insulation Panels Using Accelerated Conditions - Bae, Minjung; Kim, Sunsook; Kang, Jaesik (Materials, 2023)
International standards for vacuum insulation panels (VIPs) include an accelerated test method and a minimum quality standard for evaluating their long-term thermal performance after 25 years. The accelerated test method consists of various tests according to the characteristics of the core material and requires six months (180 days) at minimum. Herein, we propose an accelerated method for determining the long-term thermal performance of fumed-silica VIPs by shortening the required time and simplifying the procedure. Highly accelerated conditions (80 °C and 70% Relative humidity (RH)) were set for the evaluation method, using the maximum temperature (80 °C) cited in international standards and compared with the accelerated test method under accelerated conditions (50 °C and 70% RH). The inner-pressure increase rate of the VIP samples after conditioning for approximately 70 days was similar to that after conditioning for 180 days under highly accelerated and accelerated conditions, respectively. In addition, the estimated long-term thermal conductivities of the fumed-silica VIP were derived as 0.0076 and 0.0054 W/m·K under highly accelerated and accelerated conditions, respectively. These accelerated methods can be used to produce fumed-silica VIPs with similar long-term thermal conductivities. Therefore, the accelerated test method for long-term thermal performance using the highly accelerated conditions can be evaluated using a test that involves conditioning the sample for approximately 70 days under 80 °C and 70% RH.
Keywords: Accelerated method; Accelerated test methods; Accelerated tests; Condition; Fumed silicas; International standards; Long-term changes; Quality standard; Thermal Performance; Vacuum insulation panel; accelerated test; long-term change; vacuum insulation panel